2020
DOI: 10.1177/0162243920976840
|View full text |Cite
|
Sign up to set email alerts
|

Green Design Tools: Building Values and Politics into Material Choices

Abstract: Green design tools are emerging as a new response to the dilemmas that architects and designers face in preventing the toxic impacts of building construction. Environmental health advocates, scientists, and consulting firms are stepping in to provide designers with new tools—including science-based assessment methods, standards, databases, and software—intended to help structure and inform decision-making in sustainable design. We argue that green design tools play an important but largely uninvestigated role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The human eye sees objects in three dimensions and can also estimate the distance of the objects seen [ 15 ]. However, human eyes are prone to visual deviation.…”
Section: Methods Of Constructing Space Adjustment In Green Building D...mentioning
confidence: 99%
“…The human eye sees objects in three dimensions and can also estimate the distance of the objects seen [ 15 ]. However, human eyes are prone to visual deviation.…”
Section: Methods Of Constructing Space Adjustment In Green Building D...mentioning
confidence: 99%
“…(1) reducing the number of investigations; (2) expressing the opinions of experts more completely; (3) through the fuzzy application of theory, expert knowledge will be more in line with rationality and needs and (4) more economical in terms of time and cost [47]. Generally, the fuzzy Delphi method can be used to carry out the following three main steps: (1) establishing an evaluation factor set that affects decision-making; (2) collecting the opinions of experts or decision-making groups, and (3) calculating the evaluation value of the fuzzy Delphi method.…”
Section: Fuzzy Delphi Method Fdm and Fuzzy Analysis Hierarchical Proc...mentioning
confidence: 99%
“…The purpose of this research is to construct sustainable building evaluation indicators suitable for Taiwan. Based on the above literature evaluation scope and content analysis, it was found that most evaluation tools cover issues such as the internal environment of the building, the area of the building base, and the surrounding environment of the building [45,47]. The purpose of this study is to further generalize and construct a sustainable campus ecological building index that is suitable for Taiwan's geographical characteristics and has a sustainable conceptual framework such as environmental, social, and economic aspects [17,45].…”
Section: Sustainable Architecture Evaluationmentioning
confidence: 99%